1378. Reservoirs of Transmission of Resistant Gram-negative Pathogens Responsible for Neonatal Sepsis among Hospitalized Neonates in Pune, India. (31st December 2020) - Johnson, Julia; Johnson, Julia; Robinson, Matthew; Naik, Shilpa Nandkumar; Patil, Sunil; Kulkarni, Rajesh; Kinikar, Aarti; Dohe, Vaishali; Mudshinkar, Swati; Smith, Rachel; Westercamp, Matthew; Randive, Bharat; et al.
Abstract: Background: Neonatal infections with resistant Gram-negative (GN) organisms are associated with high rates of mortality, with limited antibiotic treatment options. The role of maternal colonization and environmental GN organisms as reservoirs for transmission to neonates has not been well described. Methods: We performed a prospective cohort study from October 12, 2018, until October 31, 2019, to describe the role of maternal and environmental GN colonization in BSI among neonates admitted to the neonatal intensive care unit (NICU) at a tertiary care center in Pune, India. Women admitted to Labor & Delivery with risk factors for neonatal sepsis who provided consent were enrolled and their neonates were followed until hospital discharge. For neonates who developed bloodstream infection (BSI), colonization with resistant GN organisms was assessed in their mothers from frozen vaginal and rectal swabs collected at enrollment and at delivery and in the neonates from frozen skin swabs and peri-rectal swabs collected at day of life (DOL) 0, 3, 7, and weekly until discharge. Environmental colonization was assessed with weekly sampling of unit sinks and the immediate neonatal care environment. Colonization samples were processed to identify organisms that matched neonatal blood culture isolates. Results: 953 women were enrolled, of whom 741 (78%) received antepartum antibiotics. Among 987 live born neonates, 12 (1%) died in the delivery room and 257 (26%) required NICU admission. Among neonates admitted to the NICU, 143 (56%) had at least one blood culture, of which 28 (20%) were positive; 21 (75%) had a GN BSI. The most common cause of neonatal BSI was Klebsiella pneumoniae, and 8 (38%) GN BSI were due to a carbapenem-resistant organism. No organism isolated from maternal samples matched organism and resistance pattern from neonatal blood culture. Matching strains were found in unit sinks and neonatal rectal and skin samples (Figure 1). Organism recovery from swabs and match to bloodstream isolate by sample source and time of collection from birth Conclusion: Among neonates born to mothers with risk factors for neonatal sepsis, GN organisms were the most common cause of neonatal BSI. Environmental and neonatal colonization may represent important reservoirs of transmission for these pathogens among neonates hospitalized in a tertiary care NICU in Pune, India. Disclosures: All Authors : No reported disclosures